2016
DOI: 10.1371/journal.pone.0152134
|View full text |Cite
|
Sign up to set email alerts
|

The Hemagglutinin of Bat-Associated Influenza Viruses Is Activated by TMPRSS2 for pH-Dependent Entry into Bat but Not Human Cells

Abstract: New World bats have recently been discovered to harbor influenza A virus (FLUAV)-related viruses, termed bat-associated influenza A-like viruses (batFLUAV). The internal proteins of batFLUAV are functional in mammalian cells. In contrast, no biological functionality could be demonstrated for the surface proteins, hemagglutinin (HA)-like (HAL) and neuraminidase (NA)-like (NAL), and these proteins need to be replaced by their human counterparts to allow spread of batFLUAV in human cells. Here, we employed rhabdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
28
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 71 publications
3
28
1
Order By: Relevance
“…In brief, 293T cells transfected with expression vectors for MERS-CoV S, VSV-G (positive control) or empty expression vector (negative control) were inoculated with VSV*ΔG-fLuc for 1 h before being washed with PBS and further incubated for 16 h with culture medium that was supplemented with anti-VSV-G antibody (I1, mouse hybridoma supernatant from CRL-2700; ATCC) (except for cells expressing VSV-G). The produced VSVpp were inoculated onto BHK-21 cells expressing WT or mutant DPP4, or no DPP4 (empty expression vector, negative control) and incubated for 16-18 h before fLuc activity in cell lysates was quantified as an indicator for transduction efficiency using the Beetle-Juice kit (PJK) and a plate luminometer (Hidex) [41].…”
Section: Generation Of Rhabdoviral Pseudotypes and Transduction Studiesmentioning
confidence: 99%
“…In brief, 293T cells transfected with expression vectors for MERS-CoV S, VSV-G (positive control) or empty expression vector (negative control) were inoculated with VSV*ΔG-fLuc for 1 h before being washed with PBS and further incubated for 16 h with culture medium that was supplemented with anti-VSV-G antibody (I1, mouse hybridoma supernatant from CRL-2700; ATCC) (except for cells expressing VSV-G). The produced VSVpp were inoculated onto BHK-21 cells expressing WT or mutant DPP4, or no DPP4 (empty expression vector, negative control) and incubated for 16-18 h before fLuc activity in cell lysates was quantified as an indicator for transduction efficiency using the Beetle-Juice kit (PJK) and a plate luminometer (Hidex) [41].…”
Section: Generation Of Rhabdoviral Pseudotypes and Transduction Studiesmentioning
confidence: 99%
“…Exposure of recombinant HL17 and HL18 to low pH did not render the proteins sensitive to degradation by trypsin, in contrast to conventional HA subtypes (11). However, infection of bat cells with HL-pseudotyped VSV occurred in a pH-dependent manner (12,13). Using the same approach, it was also shown that proteolytic activation of the viral glycoproteins is essential to obtain infectious pseudotyped viruses (12,13).…”
mentioning
confidence: 98%
“…However, infection of bat cells with HL-pseudotyped VSV occurred in a pH-dependent manner (12,13). Using the same approach, it was also shown that proteolytic activation of the viral glycoproteins is essential to obtain infectious pseudotyped viruses (12,13). Moreover, HL17-and HL18-pseudotyped viruses revealed a restricted cell tropism, because only certain bat cell lines were found to be susceptible to infection.…”
mentioning
confidence: 99%
See 2 more Smart Citations